Effect of B2O3 addition on optical properties of Zirconium and Hafnium tetrafluorides in polycrystalline and thin film states - Zinchenko, V.F.; Volchak, G.V.; Mozkova, O.V.; Yeriomin, O.H.; Doha, P.H. (Physics and Chemistry of Solid State, 2023)
For the first time, the effect of B2O3 additive on the IR transmission spectra of ZrF4 and HfF4 samples and the optical properties of the coatings obtained from them was investigated. A significant difference in the shape of the absorption bands and the position of the vibration peaks of the Zirconium tetrafluoride and Hafnium tetrafluoride bonds was revealed. An assumption is made about the influence of ZrF4 polymorphism on the ratio of the vapor pressures of the specified compounds in the region of the conditional temperature of evaporation in a deep vacuum. The positive effect of the B2O3 additive on the rate of evaporation of system samples and condensation on substrates is shown. The values of the refractive indices of the coatings are about 1.53. An exception is the refractive index of the HfF4 coating (1.57), which can be attributed to the alternative (monoclinic) syngony of its crystal structure.